PENGARUH DESAIN PEKERJAAN DAN PEMBERDAYAAN PSIKOLOGIS PEGAWAI TERHADAP KINERJA DENGAN MOTIVASI SEBAGAI VARIABEL MEDIASI - Arija Buana Jiwa; Hendra Lukito; Harif Amali Rivai (Journal Publicuho, 2024)
This research aims to see the influence of service quality and customer perceived value on customer This research aims to see the influence of job design and employee psychological empowerment on performance with motivation as a mediating variable for BPKP Representative Auditors in West Sumatra Province. The population is all BPKP Representative auditors from West Sumatra Province with a total of 93 people. The sample in the study was the entire population. Data analysis technique using Structural Equation Modeling (SEM) using Smart PLS. Hypothesis testing uses one-tailed statistical analysis, the hypothesis is accepted if the t-statistic value is > 1.65 and the significance value is < 0.05. The research results show that there is no significant influence between job design on auditor performance, there is no significant influence between job design on motivation. There is a positive and significant influence between psychological empowerment on performance, there is a positive and significant influence between motivation on performance and there is a positive and significant influence between psychological empowerment on motivation. Meanwhile, motivation does not mediate the influence of work design on auditor performance and does not mediate the influence of psychological empowerment on performance.